Myocardial Injury Induced by the Long Acting Beta2 Adrenergic Agonist Clenbuterol - Shafrir, Asher; Leibowitz, David W; Alcalai, Ronny; Elitzur, Yair; Muszkat, Mordechai (Cardiology and Cardiovascular Medicine, 2019)
Abstract not available in the source database.